ChemInform Abstract: Bicatalytic Allylation—Cross‐Methathesis Reactions as γ‐Carbonyl Cation Equivalents. Issue 1 (3rd January 2013) - Henkie, Jake R.; Dhaliwal, Sugadar; Green, James R.
Abstract This one‐pot, bicatalytic indium(III) allylation‐cross metathesis protocol may be responsible for the formation of products corresponding to the reaction of γ‐carbonyl cations with arene nucleophiles.